Evaluation of the KirkPatrick Model of the Basic Leadership Training Program (LDK) at the Student Council in Kediri City - Budi Pangesti, Aliffanur; Wardatul Hamidah, Leny; Huda Purnomo, Nurul (Studia Manageria, 2024)
This study aims to evaluate the effectiveness of the Student Council Leadership Basic Training (LDK) program at MA Al Huda, Kota Kediri, East Java. The subjects of the study were 14 training participants who were members of the student council (OSIS). The research employed a descriptive qualitative method using the KirkPatrick Evaluation Model, which encompasses four stages: Reaction, Learning, Behavior, and Results. Data were collected through interviews, observations, and document analysis, then analyzed to assess the success of the training in developing the participants' leadership qualities. The findings revealed that in the Reaction stage, participants expressed satisfaction with the training materials, facilities, and the competence of the instructors. In the Learning stage, participants demonstrated increased understanding of the material, as evidenced by pre-test and post-test results showing an 85.71% improvement. In the Behavior stage, positive changes were observed in participants' attitudes, public speaking skills, and ability to apply the knowledge to organizational tasks. In the Results stage, the training had a positive impact on the participants' performance, with an 80% improvement in information and organizational skills. In conclusion, the LDK program at MA Al Huda Kota Kediri effectively enhanced the leadership competencies of the participants and supported the sustainability of the organization.